(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Coffee Land is one of the coffee shops that introduce the local brand of coffee beans in the market and support the local farmers. In the past decade, the Philippines became one of the highest importers of coffee beans because the Philippines is one of few countries that produce four coffee varieties commercially, namely, Arabica, Liberica or Kapeng Barako, Excelsa, and Robusta. Coffee Land caters to people who love to drink coffee and taste different flavors that are made from various cities and regions in the Philippines and is a well-known coffee business that uses the local brand of coffee beans. Therefore, the researchers came up with this business because we want to promote our coffee bean product and its benefits. By using the local brands of coffee beans, we are creating a different product from coffee in the market. As Filipinos, we want to help to increase the profit of local workers by promoting their products to other coffee shops in the Philippines and other countries. The research method of design utilized in the study was quantitative analysis. The participant of the study sampled 100 respondents in the area of V. Luna Avenue, Diliman, Quezon City on August 6, 2019, to determine the accessibility of the place and product on the area. Based on the research, Coffee Land is feasible in the market because most of the people within the area drink coffee daily. The owners know how to run the entire business. Coffee Land used social media to promote and advertise the business. Local farmers in the coffee bean business had an opportunity to promote their local production of coffee beans in the market. Results can be forwarded to improve the business to help Coffee Land continue to reach the demand and expectation of the customers to teach the importance of our local brand of coffee beans. The management will continue to operate and handle the business until it succeeded and to be a popular business in the market of a local brand of raw material on coffee shop business in the Philippines.